Morphometric and histologic characterization of alveolar bone from hypertensive patients - Fabris, André Luís da Silva [UNESP]; Mulinari-Santos, Gabriel [UNESP]; Hassumi, Jaqueline Suemi [UNESP]; Freire, Alexandre Rodrigues; Faverani, Leonardo Perez [UNESP]; Gruber, Reinhard; Okamoto, Roberta [UNESP] (Wiley, 2017)
Background: Hypertension is considered a risk factor in implant dentistry but the underlying reasons remain unclear. It may be that hypertension has a negative impact on the local bone quality. Purpose: Here we evaluated the structural and histological parameters of bone collected from hypertensive patients treated by antagonists of the renin-angiotensin system, and of bone collected from normotensive patients. Material and methods: A total of 30 patients were referred for rehabilitation with dental implants to be placed in the posterior mandible. The first group were hypertensive patients treated with RAS antagonists. The second group were normotensive patients not taking medication. Bone biopsies collected during implant installation were subjected to analysis. Micro CT revealed the structural parameters. Histological analyses together with immunohistochemical staining of osteogenic markers were performed. Results: The structural parameters of bone volume, trabecular thickness, trabecular number, separation of the trabecular, and total porosity were similar between the 2 groups (P >.05). The histological appearance of bone derived from hypertensive patients was normal. The staining pattern of Runx-2, osteopontin, and osteocalcin were comparable in both groups. Conclusions: These observations suggest that hypertensive patients treated with renin-angiotensin system antagonists have regular alveolar bone with respect to bone structure and histological parameters.
Keywords: bone; dental implant; hypertension